Manajemen Nyeri Low Back Pain Pada Warga Kelompok Dawis Cempaka Mojosongo - Setyaningsih, Rahayu; Suyanto, Sutriono (Cahaya Pengabdian, 2024)
Low Back Pain (LBP) or Lower Back Pain (NPB) is a health problem that is often encountered in society. Almost 70-80% of people in developed countries have experienced LBP. Every year 15-45% of adults suffer from LBP, and one in 20 sufferers must be hospitalized due to an acute attack. LBP often occurs at the age of 35-55 years and almost 80% of people in industrialized countries have experienced it. Obesity, stress, and sometimes depression can result in LBP. Chronic LBP sufferers usually experience dependence on several types of analgesics, which is the most common reason to seek treatment. The aim of the activity is to teach the public how to treat lower back pain non-pharmacologically. The educational method is by lecture and discussion/question and answer. The target of the activity is adults 30 years and over. The organizers of the activity were 3 lecturers and students from the Insan Husada Surakarta Polytechnic. The target location is at Dasa Wisma Cempaka Mojosongo Jebres Surakarta. A total of 25 Dawis residents took part in this activity on November 5 2023 for 60 minutes. The outreach activities went well according to the target and plan, and all Dawis residents were able to take part in the outreach activities on low back pain management. The level of knowledge of Dawis Cempaka residents pre and post has improved.